Meliponini biodiversity and medicinal uses of the honey from El Oro province in Ecuador. - Vargas, Oliverio (2015)
products are used in healing. Diverse remedies consist on pot-honey alone or mixed with infusions. This set of medicinal uses were informed in El Oro province by Ecuadorian stingless bee keepers known as meliponicultors in Latin America. bruises, tumors, ocular cataracts, pterygium, inflammation, infections, varicose veins, cleaning blood after childbirth, kidney diseases, tumor, wound healing, and soothing balm before sleeping. Scaptotrigona ederi named “catiana” or “catana” is the most frequent bee in the visited cantons Las Lajas, Balsas, Piñas, and Zaruma. Other important stingless bees are Melipona indecisa “cananambo”, Melipona mimetica “bermejo”, Nannotrigona cf. perilampoides “pitón”, and Paratrigona aff. eutaeniata “pirunga”. A bioprospective research will follow to value this ancient tradition and the honey processed in cerumen pots, with sound inclusion in the Ecuadorian honey regulation NTE INEN 1572, currently under revision.